RESULTS OF THE APPLICATION OF ENDOSURGICAL TECHNOLOGIES IN THE DIAGNOSIS AND TREATMENT OF EARLY INTRAABDOMINAL COMPLICATIONS IN POSTOPERATIVE PERIOD - Yusubov, I.A.; Sharifov, E.Y. (World of Medicine and Biology, 2024)
The purpose of the study was to improve the treatment results of early intra-abdominal complications by optimizing diagnostic methods and surgical tactics. The main group consisted of 1326 patients who preferred the active use of minimally invasive technologies in choosing surgical tactics and in the treatment process. The control group included 342 patients. In this group, relaparotomy was preferred for the correction of postoperative intra-abdominal complications. Relaparotomy on demand was performed in 145 (10.9 %) patients due to the obvious impossibility of endosurgical elimination of the complication at the preoperative stage. Mortality when using minimally invasive technologies in the diagnosis and treatment of intra-abdominal complications arising after abdominal surgeries was 5.3 %, and when performing relaparotomy to correct complications - 27.8 %. The average length of stay of patients in the clinic after repeated operations using minimally invasive technologies was 14.2±5.3 days and after relaparotomy – 25.4±7.3 days. Thus, the use of the algorithm for diagnosing complications using minimally invasive technologies allows for the timely implementation of the capabilities of endosurgical and traditional technologies and thereby improves the treatment results of postoperative abdominal complications.